Aligning multiple choice assessments with active learning instruction: More accurate and equitable ways to measure student learning. Issue 1 (2nd January 2023) - Teasdale, Rachel; Aird, Hannah
Abstract: In response to geoscience education research and calls for the need to reform STEM teaching in higher education, many geoscience faculty are adopting research-based pedagogies to improve student learning in their courses. Our own effort to reform our introductory geology course included daily student-centered activities and other reforms we expected would result in improved student performance, but did not. This paper describes our evaluation of student performance on multiple choice questions (MCQs), which are the largest component of student grades in the course. Student scores were highest on MCQs that were aligned with the style in which students learned material and that required students to interact with the question (active questions) rather than just regurgitating information (passive questions). We also examined whether the style of MCQs impacted student scores equitably and found that the grades of all students would have improved if we had asked MCQs that were aligned and active, and the improvements were equitable, but final grades remain biased.